Psychometric Properties of the Psychological State Test for Athletes (TEP) - Díaz-Tendero, Patricia; Pérez-Llantada, M. Carmen; López de la Llave, Andrés (Frontiers in Psychology, 2020)
This study has two objectives: to validate an adapted online version of the Psychological State Test (TEP, in its Spanish acronym); and to assess differences in pre-competitive psychological state profiles between amateur and professional athletes in team sports. The TEP questionnaire is an instrument which is used to assess, in a quick and simple fashion, the psychological state of athletes prior to competing. Its psychometric properties were evaluated by means of an analysis of internal consistency, an Exploratory Factor Analysis and a Confirmatory Factor Analysis. The EFA’s results showed a factorial structure consisting of two principal factors and reliability coefficients, both globally and at the factor level, which can be considered acceptable (global = 0.81; Factor 1 = 0.85; and Factor 2 = 0.73). The CFA confirmed the model proposed by the EFA so that the items were distributed around these factors, giving rise to one factor which includes variables that have a positive relationship with performance, and another with variables that negatively affect performance. Meanwhile, regarding the difference between the pre-competitive psychological state of amateurs and professionals, professional athletes presented higher levels of Motivation (p= 0.5 and d= -0.23). It is concluded that the TEP is a suitable tool for the evaluation of pre-competitive psychological states. However, in future research, this study should be complemented by analysing the TEP’s predictive validity in terms of the performance of athletes and/or teams, as well as its use as a tool available to athletes and coaches.